Manifestation of Anthropomorphism in Modern Kazakh Story (based on Askar Altai’s story «Centauri») - Sydykbaeva А.; Aimukhambet Ж. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
Anthropomorphisms are an artistic method in art, a literary device. However, to date, anthropomorphisms have changed their form, acquired a symbolic meaning. And they began to express deeper thoughts and perform an artistic and aesthetic function in the works. The article discusses this aspect of anthropomorphism in the modern Kazakh story. A review was also made on frequently occurring phenomena of anthropomorphic knowledge in the folklore of the Kazakh people and in everyday use. By analyzing the combinations of mythology and artistry, the specificity and meanings of mythological and anthropomythological images in modern literary development were determined. And the ways of figurative representation of the world were considered. We believe that the transformation of mythical stories and heroes in time in the stories of the writer Askar Altai, his skill in using this method is one of the actual problems of the stories of the modern period, which requires analysis from a new point of view